Physiological, Performance and Perceptual Effects of Acute Intake of an L-Arginine and L-Citrulline Beverage Prior to a Repeated Bout of Intensive Running Among University Soccer Players - Siphamandla Nyawose; Rowena Naidoo; Nenad Naumovski; Andrew J. McKune (Nutraceuticals)
The purpose of this study was to determine whether a combined L-arginine and L-citrulline beverage can enhance total nitric oxide (NOx), as well as physiological (cardiopulmonary metrics) and perceptual (rate of perceived exertion) responses to a repeated bout of high-intensity exercise among university soccer players. Thirty male soccer players were included in a randomized double-blind, placebo-controlled, parallel design. Participants performed two bouts of high-intensity running, spaced two hours apart. Forty minutes before the second bout only, participants consumed a 500 mL beverage containing 6 g L-arginine and 6 g L-citrulline (n = 15) or placebo (n = 15). Blood NOx concentration was measured immediately before and after both bouts. There was no significant increase in NOx or significant interaction effects for physiological, performance, or perceptual variables between the L-arginine/L-citrulline and placebo groups. The peak volume of oxygen uptake of the L-arginine/L-citrulline group was significantly higher in the second compared with the first exercise bout (54.92 ± 4.81 vs. 50.54 ± 9.22 mL/kg/min; p = 0.01). In the second bout of exercise, time to exhaustion in the L-arginine/L-citrulline group increased by 8.5% (~60 s) compared to the first. In conclusion, these results suggest that a single dose of L-arginine/L-citrulline beverage did not increase NOx yet seemed to impact aerobic metabolism in university soccer players.